2017
DOI: 10.1121/1.4973849
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of noise and room acoustics on vocal effort in simulated classrooms

Abstract: This work investigated the relationships between room acoustics, background noise level, and vocal effort of a speaker in simulated classrooms of various volumes. Under simulated acoustic environments, talkers adjusted their vocal effort linearly with the voice support, i.e., the degree of amplification offered by the room to the voice of a speaker, at his own ears. The slope of this relationship, called the room effect, of -0.24 dB/dB was significant only in the case of the highest noise levels of 62 dB. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…This information is important because it can guide vocal health promotion actions helping to decrease the occurrence of voice disorders and improve speakers´voice-related quality of life. For instance, among occupational voice users, such as teachers and call center operators, considering their high risk of developing voice disorders associated with their working conditions (Pelegrín-García and Brunskog, 2012;Cantor-Cutiva et al, 2013;Bottalico et al, 2015;Bottalico et al, 2016a;Cantor-Cutiva and Burdorf, 2016;Bottalico et al, 2017a;Banks et al, 2017;Cipriano et al, 2017;Cantor-Cutiva et al, 2019;Carrillo-Gonzalez et al, 2019), it is determinant to identify specific elements that can help to improve "healthy" occupational voice use. Therefore, knowing that sidetone may help to decrease SPL and increase self-perceived voice comfort and control, speech and language pathologists at the workplaces may train occupational voice users using sidetone to strengthen voice comfort and control and reduce occupational voice misuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This information is important because it can guide vocal health promotion actions helping to decrease the occurrence of voice disorders and improve speakers´voice-related quality of life. For instance, among occupational voice users, such as teachers and call center operators, considering their high risk of developing voice disorders associated with their working conditions (Pelegrín-García and Brunskog, 2012;Cantor-Cutiva et al, 2013;Bottalico et al, 2015;Bottalico et al, 2016a;Cantor-Cutiva and Burdorf, 2016;Bottalico et al, 2017a;Banks et al, 2017;Cipriano et al, 2017;Cantor-Cutiva et al, 2019;Carrillo-Gonzalez et al, 2019), it is determinant to identify specific elements that can help to improve "healthy" occupational voice use. Therefore, knowing that sidetone may help to decrease SPL and increase self-perceived voice comfort and control, speech and language pathologists at the workplaces may train occupational voice users using sidetone to strengthen voice comfort and control and reduce occupational voice misuse.…”
Section: Discussionmentioning
confidence: 99%
“…Vocal comfort can be defined as a subjective attribute that is directly correlated to the positive evaluation of the room for speech production and to the perceived support. Vocal comfort has been shown to be negatively correlated to the feeling of having to raise the voice and to the tiredness after speaking for a long time period in the room (Pelegrín-García et al, 2014;Cipriano et al, 2017). A questionnaire investigation showed that voice comfort is more closely related to the perceived noise annoyance than to the perceived room reverberance.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers have quoted various factors that can be associated with teacher's voice in a classroom. Some of these are working posture, teaching core subjects, classroom noise, voice ergonomic factors, presence or absence of sound amplification, teachers with voice problems, classroom capacity, gender, stress, speech style, room acoustics, vocal fatigue, acoustic environment, vocalisation time, reverberation and combined effect of noise and acoustics . These factors may act independently or may be linked to each other.…”
Section: Discussionmentioning
confidence: 99%
“…21 presence or absence of sound amplification, 22 teachers with voice problems, 23 classroom capacity, 24 gender, 25 stress, 26 speech style, room acoustics, vocal fatigue, 27 acoustic environment, 28 vocalisation time, 29 reverberation 30 and combined effect of noise and acoustics. 31 These factors may act independently or may be linked to each other. A brief summary of these studies is given in Table 8.…”
Section: Discussionmentioning
confidence: 99%
“…A review of literature suggests that most speech tasks used in experiments only capture a part of the changes in speech mechanism relevant to speech intelligibility such as speech sound pressure level 11 and other speech parameters due to the effect of reverberation and noise 12,55 or have been done in simulated environments. 56 With respect to classroom environments, it becomes important to study any differences observed in global speech characteristics and vowel articulation characteristics of talkers from real classroom environments, when exposed to different room acoustical conditions and when using the natural mode of speech delivery, that is, lecturing. In this study, natural modifications in speech in terms of correlates of speech intelligibility were studied within and across talkers, when eliciting a typical lecture mode of speech as against reading a passage and also under typical classroom noise, reflecting the circumstances associated with communicative demands typical of classroom discourse.…”
Section: Global Speech Characteristicsmentioning
confidence: 99%